Predictive value of C-reactive protein for radiographic spinal progression in axial spondyloarthritis in dependence on genetic determinants of fibrin clot formation and fibrinolysis. Issue 2 (29th June 2021) - Hoppe, Berthold; Schwedler, Christian; Haibel, Hildrun; Verba, Maryna; Proft, Fabian; Protopopov, Mikhail; Heuft, Hans-Gert; Rios Rodriguez, Valeria; Edelmann, Anke; Rudwaleit, Martin; Sieper, Joachim; Poddubnyy, Denis
Abstract : Objective: Genetic determinants of fibrin clot formation and fibrinolysis have an impact on local and systemic inflammatory response. The aim of the present study was to assess whether coagulation-related genotypes affect the predictive value of C-reactive protein (CRP) in regards of radiographic spinal progression in axial spondyloarthritis (axSpA). Methods: Two hundred and eight patients with axSpA from the German Spondyloarthritis Inception Cohort were characterised for genotypes of α-fibrinogen, β-fibrinogen (FGB) and γ-fibrinogen, factor XIII A-subunit (F13A) and α2 -antiplasmin (A2AP). The relation between CRP levels and radiographic spinal progression defined as worsening of the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS) by ≥2 points over 2 years was assessed in dependence on the respective genetic background in logistic regression analyses. Results: Overall, CRP was associated with mSASSS progression ≥2 points: time-averaged CRP ≥10 mg/L, OR: 3.32, 95% CI 1.35 to 8.13. After stratification for coagulation-related genotypes, CRP was strongly associated with mSASSS progression in individuals predisposed to form loose, fibrinolysis-susceptible fibrin clots (FGB rs1800790GG, OR: 6.86, 95% CI 2.08 to 22.6; A2AP 6Trp, OR: 5.86, 95% CI 1.63 to 21.0; F13A 34Leu, OR: 8.72, 95% CI 1.69 to 45.1), while in genotypes predisposing to stable fibrin clots, the association was absent or weak (FGB rs1800790A, OR: 0.83, 95% CI 0.14 to 4.84; A2AP 6Arg/Arg, OR: 1.47, 95% CI 0.35 to 6.19; F13A 34Val/Val, OR: 1.72, 95% CI 0.52 to 5.71). Conclusions: Elevated CRP levels seem to be clearly associated with radiographic spinal progression only if patients are predisposed for loose fibrin clots with high susceptibility to fibrinolysis.